Predicting railway-induced ground-borne noise from the vibration of radiating building elements using power-based building acoustics theory. Issue 1 (2nd January 2018) - Villot, Michel; Jean, Philippe; Grau, Loïc; Bailhache, Simon
ABSTRACT: Noise measured inside buildings close to railway lines is often a mixture of ground-borne noise and airborne noise. Predicting ground-borne noise from vibration measurements and comparing the result to noise measurements may be useful to identify ground-borne noise. In this paper, the prediction is performed using the building acoustics theory and a power-based parameter called radiation efficiency. Due to the low-frequency range of ground-borne noise where both building elements and rooms have strong modal behaviour, the usual values of radiation efficiency – either measured or calculated under diffuse field conditions – cannot be used anymore. However, this parameter can still be measured or calculated using numerical models, but it becomes situation dependent. In this paper, the values of radiation efficiency useable at low frequencies are calculated and their spectra discussed. Rough approximations are then proposed, thus leading to simplified formulae, useable at the engineering level for prediction but only valid under certain assumptions.